A study of quality of life among patients undergoing mastectomy for malignant breast lesions - Shastri, Apoorv; Agarwal, Manoj; Patel, Hardik; Sharma, Avantika (International Surgery Journal, 2017)
Background: To evaluate quality of life of females after mastectomy and factors affecting the same, in various domains of life, and to assess whether a policy of mastectomy is practical or pragmatic in the scenario of low socioeconomic status prevalent in our region. Methods: Two hundred and forty post-operative mastectomized patients were clinically examined and subjected to a questionnaire designed by WHOQOL-BREF along with an ethically cleared questionnaire prepared according to the local prevailing conditions and Quality of Life was evaluated. Results: 52% patients reported no change in body image, only 2% patients reported depression. The total score of the quality of life was good for 40% of the patients with score of 96-130, followed by 55% with moderate 61-95 and only 5% patients with poor with score of <60. Conclusions: In developing countries like India where, there are no proper facilities for advanced haematological and radiological investigations, there is a severe lack of compliance between doctor and patient and there are no facilities for adjuvant and neo-adjuvant treatment, surgeons are forced to choose mastectomy as the surgery of choice for malignant breast lesions.